Short sleep duration is associated with teacher-reported inattention and cognitive problems in healthy school-aged children - Michaelsen S (Dove Medical Press, 2012)
Reut Gruber1,2, Sonia Michaelsen1,2, Lana Bergmame2, Sonia Frenette3,4, Oliviero Bruni5, Laura Fontil2, Julie Carrier3,41Department of Psychiatry, McGill University, 2Attention, Behavior and Sleep Lab, Douglas Mental Health University Institute, 3Centre du Sommeil et des Rythmes Biologiques, Hôpital du Sacré-Coeur de Montréal, 4Departement de Psychologie, Université de Montréal, Montreal, QC, Canada; 5Child Neuropsychiatry Unit, University of Rome, Rome, ItalyPurpose: Pediatric, clinical, and research data suggest that insufficient sleep causes tiredness and daytime difficulties in terms of attention-focusing, learning, and impulse modulation in children with attention deficit hyperactivity disorder (ADHD) or in those with ADHD and primary sleep disorders. The aim of the present study was to examine whether sleep duration was associated with ADHD-like symptoms in healthy, well-developing school-aged children.Patients and methods: Thirty-five healthy children (20 boys, 15 girls), aged 7–11 years participated in the present study. Each child wore an actigraphic device on their nondominant wrist for two nights prior to use of polysomnography to assess their typical sleep periods. On the third night, sleep was recorded via ambulatory assessment of sleep architecture in the child's natural sleep environment employing portable polysomnography equipment. Teachers were asked to report symptoms of inattention and hyperactivity/impulsivity on the revised Conners Teacher Rating Scale.Results: Shorter sleep duration was associated with higher levels of teacher-reported ADHD-like symptoms in the domains of cognitive problems and inattention. No significant association between sleep duration and hyperactivity symptoms was evident.Conclusion: Short sleep duration was found to be related to teacher-derived reports of ADHD-like symptoms of inattention and cognitive functioning in healthy children.Keywords: ADHD-like symptoms, sleep duration, inattention, hyperactivity, impulsivity, healthy school-aged children